Chemodivergent dehydrogenative coupling of alcohols by 3d metal catalysts - Bansal, Sadhna; Punji, Benudhar (ChemCatChem, 2024)
Chemodivergent synthesis by transition metal catalysts is a straightforward and sustainable approach to achieving valuable organic compounds. Especially, the chemodivergent dehydrogenative couplings of alcohols with organic motifs to develop various saturated and unsaturated compounds are highly environmentally benign due to the reduced waste generation. In this concept review, we presented the 3d transition metal (Mn, Fe, Co, and Ni)-catalyzed chemodivergent synthesis of imines and amines, saturated and unsaturated carbonyl/alcohol compounds, saturated and unsaturated nitriles, N-heterocycles, and N-/C-alkylated indoles. The discussed reaction commanded two or three different products with high chemoselectivity by changing specific reaction parameters, but keeping the catalyst unchanged. Generally, the acceptorless dehydrogenative coupling (ADC) provides unsaturated moieties, whereas the borrowing-hydrogen (BH) process results in saturated compounds. Text for Table of Contents: An overview of the chemodivergent dehydrogenative coupling of alcohols by the Earth-abundant transition metal catalysts is discussed. image
Keywords: 3d metals; Alcohols; chemodivergent; dehydrogenative coupling; heterocycles